Efficient Synthesis of Benzospirocyclohexadienones via PIFA-Promoted Intramolecular Dearomative Spiroannulation - An, Xinkun; Zhang, Tingting; Ma, Haoyun; He, Xie; Wang, Mingan (Synthesis, 2024)
A rapid and convenient method for the synthesis of differently substituted spiro[cyclohexane-1,1′-isochromane]-2,5-dien-4-one derivatives via phenyliodine(III) bis(trifluoroacetate) (PIFA)-promoted intramolecular oxidative dearomatization at the para position is disclosed, with the aim of building a library of new spirocyclohexadienone scaffolds. Subsequently, this strategy is modified to access novel cyclohexanedienone-containing polycyclic compounds.
Keywords: spirocyclic compounds; cyclohexadienones; hypervalent iodine(III) reagents; phenyliodine(III) bis(trifluoroacetate); dearomatization